Noise in multiple sclerosis: unwanted and necessary. (19th June 2014) - Bordi, Isabella; Ricigliano, Vito A. G.; Umeton, Renato; Ristori, Giovanni; Grassi, Francesca; Crisanti, Andrea; Sutera, Alfonso; Salvetti, Marco
Abstract As our knowledge about the etiology of multiple sclerosis (MS) increases, deterministic paradigms appear insufficient to describe the pathogenesis of the disease, and the impression is that stochastic phenomena (i.e. random events not necessarily resulting in disease in all individuals) may contribute to the development of MS. However, sources and mechanisms of stochastic behavior have not been investigated and there is no proposed framework to incorporate nondeterministic processes into disease biology. In this report, we will first describe analogies between physics of nonlinear systems and cell biology, showing how small‐scale random perturbations can impact on large‐scale phenomena, including cell function. We will then review growing and solid evidence showing that stochastic gene expression (or gene expression "noise") can be a driver of phenotypic variation. Moreover, we will describe new methods that open unprecedented opportunities for the study of such phenomena in patients and the impact of this information on our understanding of MS course and therapy.